Amino Acid Content Profile and Antioxidant Activity Test of Spirulina Platensis Bioactive Protein Extract Using DPPH Method - Tahirah Hasan; Nur Ida; Yasnidar Yasir (Jurnal Penelitian Pendidikan IPA, 2025)
The study of Amino Acid Content Profile and Antioxidant Activity Test of Spirulina platensis Bioactive Protein Extract with DPPH Method has been conducted. This study aims to determine the protein content and IC50 value of Spirulina platensis bioactive protein extract with DPPH method. The research method includes extraction of Spirulina platensis powder using buffer A solvent. Determination of protein content with Lowry method using Bovine Serum Albumin (BSA) as standard solution and antioxidant activity test with DPPH method. The results of the analysis of protein content of Spirulina platensis extract obtained a level of 39.51%. The antioxidant activity test against DPPH free radicals showed that Spirulina platensis protein extract has antioxidant activity with IC50 value of 599.17 ± 3.75 ppm.